The granular landscape of health disparities: a socio-spatial examination of chronic disease prevalence within New York City's community districts - Martin-Ikpe, Cordelia; Were, Lawrence P. O.; Okoror, Titilayo A. (Frontiers in Environmental Health, 2024)
This study investigates the relationship between neighborhood Socioeconomic Position (SEP) and the prevalence of hypertension and coronary heart disease (CHD) across New York City’s community districts. By employing a comprehensive SEP measure derived from the Modified Darden-Kamal Composite Socioeconomic Index, alongside health outcome data from the CDC PLACES dataset, this research aims to uncover nuanced health disparities that might be overlooked in broader analyses. Utilizing a linear mixed-effects model (LMM), the study identified a significant negative association between SEP and both hypertension and CHD, with higher SEP levels corresponding to lower prevalence rates of these conditions. Further exploration through an interaction model revealed that the relationship between SEP and CHD is more complex than its relationship with hypertension, indicating that different underlying factors may influence these health outcomes. The findings suggest that in certain community districts, SEP alone does not fully account for the high prevalence of CHD and hypertension, highlighting the potential role of other factors, such as environmental conditions and access to healthcare. These results emphasize the need for targeted public health interventions that consider not only socioeconomic factors but also the specific local context and conditions. The study advocates for a neighborhood-focused approach to public health strategies, particularly in areas where traditional socioeconomic indicators may not fully capture the drivers of poor health outcomes.